2004
DOI: 10.1016/j.ydbio.2004.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of ezrin on threonine T567 plays a crucial role during compaction in the mouse early embryo

Abstract: The preimplantation development of the mouse embryo leads to the divergence of the first two cell lineages, the inner cell mass and the trophectoderm. The formation of a microvillus pole during compaction at the eight-cell stage and its asymmetric inheritance during mitosis are key events in the emergence of these two cell populations. Ezrin, a member of the ERM protein family, seems to be involved in the formation and stabilization of this apical microvillus pole. To further characterize its function in early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 40 publications
1
67
0
3
Order By: Relevance
“…This linker function makes ezrin essential for many fundamental cellular processes, including the determination of cell shape, polarity and surface structure, cell adhesion, motility, cytokinesis, phagocytosis and integration of membrane transport with signaling pathways (Serrador et al, 1999;Ng et al, 2001;Bretscher et al, 2002;Wu et al, 2004). Ezrin is expressed in many normal tissues and has been demonstrated to be important during embryogenesis (Dard et al, 2004;Polesello and Payre, 2004;Saotome et al, 2004). Nonetheless, the redundancy that exists between ezrin and the other ERM proteins may be sufficient to compensate for the loss of ezrin in some physiological processes.…”
Section: Introductionmentioning
confidence: 99%
“…This linker function makes ezrin essential for many fundamental cellular processes, including the determination of cell shape, polarity and surface structure, cell adhesion, motility, cytokinesis, phagocytosis and integration of membrane transport with signaling pathways (Serrador et al, 1999;Ng et al, 2001;Bretscher et al, 2002;Wu et al, 2004). Ezrin is expressed in many normal tissues and has been demonstrated to be important during embryogenesis (Dard et al, 2004;Polesello and Payre, 2004;Saotome et al, 2004). Nonetheless, the redundancy that exists between ezrin and the other ERM proteins may be sufficient to compensate for the loss of ezrin in some physiological processes.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Phosphorylation of ezrin promotes morphogenesis of apical microvilli and regulates E-cadherindependent adherent junction assembly. [13][14][15] Ezrin directly interacts with signaling enzymes such as phosphoinositide 3-kinase (PI3-kinase), and the phosphorylated tyrosine 353 (Tyr-353) residue of ezrin is regulated through the PI3-kinase/Akt pathway. 11 Ezrin is also preferentially degraded and resynthesized after oxidative stress 16 and the phosphorylation at threonine 567 (Thr-567) depends on the p38 MAP-kinase activity.…”
mentioning
confidence: 99%
“…The cytoskeleton protein ezrin is another good candidate (Louvet-Vallée et al, 2001). We have shown that phosphorylation of ezrin on T567 regulates its localization at the time of compaction and that maintenance of ezrin at the basolateral cortex at the 8-cell stage, interferes with the activity of E-cadherin and inhibits the formation of normal cell-cell contacts (Dard et al, 2004).…”
Section: Regulation Of Flatteningmentioning
confidence: 99%
“…The removal of microvilli at the basolateral membrane, is crucial to allow flattening (Dard et al, 2004). Ezrin, a cytoskeleton protein linking actin to the plasma membrane in diverse types of membrane protrusions, follows exactly the distribution of microvilli: before compaction it is distributed all around the cell cortex and during polarization, it is removed from cell-cell contacts and relocates exclusively at the apical pole of blastomeres (Louvet et al, 1996).…”
Section: Elegans Its Role In the Regulation Of The Microtubule Nementioning
confidence: 99%